(untitled) - Sagar, Putumbaka Vidya (Ansari Road, New Delhi, 2005)
Contents of material: 1/ Concepts of library classification. 2/ Philosophies of classification. 3/ Relation between classification and subject cataloguing. 4/ The disigning of classification schemes. 5/ Universal decimal classification. 6/ Decimal classification. 7/ Colon classification. 8/ Mechanical classification method. 9/ Idea plane. 10/ Facet for rounds. 11/ Conons in idea plane. 12/ Postulational procedure. 13/ Fundamental categories, arrays and chais. 14/ Notation with terminology. 15/ mechanical indexing and retrieval. 16/ Information retrieval through classification. 17/ Modes of formation. 18/ Classification in social science. 19/ Practical classification.
Keywords: Classification, Dewey decimal,Classification, Universal Decimal,Classification, Colon